TINGKAT TUTUR DALAM BUDAYA 'JAWA' DAN 'BATAK': Analisis Sosio-Pragmatik - Tobing, Roswita Lumban (Diksi, 2015)
This article is about a socio-pragmatic study on the language used by the Javanese society which has some speech levels (or unggah-ungguh in Javanese) called ngoko, krama madya, and krama inggil and the language used by the Batak society which does not have such speech levels. The difference concerning speech levels between the two societies is influenced by their traditional ways of living. The traditional Javanese society is divided into two levels: the priyayi (or the nobility) and wong cilik (or the commoner) levels. A priyayi uses ngoko in communicating with a wong cilik but the latter cannot use it in communicating with the former. In such a case, the wong cilik uses krama inggil. This seems to indicate that solidarity in the Javanese society is poor. On the other hand, the Batak society does not have such levels so that there are no speech levels in its language. Though the Batak society has many margas, which means that any members of the society having the same last name belong to the same marga and are regarded as members of the same family (the relevant term is dongan sabutuha), they are obliged to help other people who do not belong to their marga because the philosophy of the Batak society is dalihan na tolu, which explains that solidarity in the Batak society is very important. Keywords: socio-pragmatic, ways of living, speech levels, solidarity